Musical Classicism using gamification: an experience in the secondary music classroom (Per Musi, 2024)
Current national and international educational guidelines point out the importance of using different methodological strategies for the development of key competences at the end of compulsory schooling. In this respect, gamification is a teaching strategy that is conducive to the development of content and key competences in the classroom through the adaptation of game elements in the didactic proposals. In this way, we present the experience of using this methodological strategy to learn about the historical period of classicism in two classrooms in the 3rd year of Compulsory Secondary Education. The results obtained show a good acceptance and high motivation of the participating students. At the same time, it shows the possibility of investigating in greater depth aspects of musical analysis, and in the areas of listening and musical perception .